COVID-19 and social distancing: A cross-cultural study of interpersonal distance preferences and touch behaviors before and during the pandemic - Croy, I.; Heller, C.; Akello, G.; Anjum, A.; Atama, C.; Avsec, A.; Bizumic, B.; Rodrigues, R. B.; Boussena, M.; Butovskaya, M.; Can, S.; Cetinkaya, H.; et al. (Cross-Cultural Research, 2023)
The COVID-19 pandemic has led to the introduction of unprecedented safety measures, one of them being physical distancing recommendations. Here, we assessed whether the pandemic has led to long-term effects on two important physical distancing aspects, namely interpersonal distance preferences and interpersonal touch behaviors. We analyzed nearly 14,000 individual cases from two large, cross-cultural surveys – the first conducted 2 years prior to the pandemic and the second during a relatively stable period of a decreased infection rate in May-June 2021. Preferred interpersonal distances increased by 54% globally during the COVID-19 pandemic. This increase was observable across all types of relationships, all countries, and was more pronounced in individuals with higher self-reported vulnerability to diseases. Unexpectedly, participants reported a higher incidence of interpersonal touch behaviors during than before the pandemic. We discuss our results in the context of prosocial and self-protection motivations that potentially promote different social behaviors.